Strategic Polarization - Adam Kalai; Ehud Kalai (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
In joint decision making, people with common goals and similar preferences often take drastically opposing positions. In some cases, arbitrarily small discrepancies in preferences result in arbitrarily large losses in utility for all participants. An understanding of the properties of polarization may help game players and mechanism designers avoid its pitfalls.
Keywords: 330